2020
DOI: 10.1111/all.14647
|View full text |Cite
|
Sign up to set email alerts
|

Immunological imprint of COVID‐19 on human peripheral blood leukocyte populations

Abstract: Background SARS‐CoV‐2 has triggered a pandemic that is now claiming many lives. Several studies have investigated cellular immune responses in COVID‐19‐infected patients during disease but little is known regarding a possible protracted impact of COVID‐19 on the adaptive and innate immune system in COVID‐19 convalescent patients. Methods We used multiparametric flow cytometry to analyze whole peripheral blood samples and determined SARS‐CoV‐2‐specific antibody levels against the S‐protein, its RBD‐subunit, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 67 publications
9
75
5
2
Order By: Relevance
“…The study by Sterlin et al observed that elevated IgA plasmablasts shortly after the onset of symptoms of COVID-19 with the peak at the third week of the disease [23]. Plasmablast levels were also significantly elevated in COVID-19 convalescent patients [24]. Considering the TGF-b1 results together with our previous finding of serum IgA in COVID-19, the TGF-b1-IgA axis may play an important role in the pathogenesis of COVID-19.…”
Section: Discussionsupporting
confidence: 56%
“…The study by Sterlin et al observed that elevated IgA plasmablasts shortly after the onset of symptoms of COVID-19 with the peak at the third week of the disease [23]. Plasmablast levels were also significantly elevated in COVID-19 convalescent patients [24]. Considering the TGF-b1 results together with our previous finding of serum IgA in COVID-19, the TGF-b1-IgA axis may play an important role in the pathogenesis of COVID-19.…”
Section: Discussionsupporting
confidence: 56%
“…Although plenty of studies indicate the proportion or number of Tregs is increased in patients with COVID-19 (especially those with the milder disease), it was also reported that the number of Tregs is reduced in the patients. For example, it has been reported that Tregs (CD3 + CD4 + CD25 hi CD127 lo FoxP3 + ) in PBMCs were markedly decreased in severe COVID-19 patients [59][60][61]. The result of single-cell analysis showed that FoxP3 expression was remarkedly reduced in severe patients with COVID-19, although the expression of CD25 was higher [62].…”
Section: The Role Of Tregs In the Immunopathology Of Covid-19: Currenmentioning
confidence: 99%
“…It has been hypothesised that a betterpreserved immunological memory, and acquired after common cold coronavirus infection, could represent the factor highly responsible for a better prognosis, or even absence of relevant clinical symptoms, in children and young people as compared to older. Compatibly, acute SARS-CoV-2 infection leaves activated T cells and specific antibody responses [96]. Is this the first time that a coronavirus causes different symptoms in subjects of different ages?…”
Section: Inflammation and Immune Response-molecular Cross-talkmentioning
confidence: 99%